Respuesta inmune en las enfermedades del periodonto: desde salud hasta enfermedad y sus implicaciones terapéuticas (2009)
ABSTRACT: Periodontal disease is the resulting clinical expression of an inflammatory process, initiated by bacteria and perpetuated during long periods of time. A series of cellular and molecular events occur with variable complexity as soon as bacteria start to accumulate around teeth. Although bacteria are necessary for the initiation of periodontal disease, the immune response is the responsible for the periodontal breakdown. The clinical appearance of periodontal disease is the result of sequential immune events. This article reviews the most important immunological mechanisms implicated in periodontal disease and their relationship with periodontal treatment.